2003
DOI: 10.1103/physrevb.67.014411
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic relaxation in finite two-dimensional nanoparticle ensembles

Abstract: We study the slow phase of thermally activated magnetic relaxation in finite two-dimensional ensembles of dipolar interacting ferromagnetic nanoparticles whose easy axes of magnetization are perpendicular to the distribution plane. We develop a method to numerically simulate the magnetic relaxation for the case that the smallest heights of the potential barriers between the equilibrium directions of the nanoparticle magnetic moments are much larger than the thermal energy. Within this framework, we analyze in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
34
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…(18) exhibits logarithmic singularities. To prevent this nonphysical behavior of T Ω the regularity condition dT Ω /dθ ′ | θ ′ =π(1−Ω)/2 = 0 must hold [23]. In order to derive the boundary condition for eq.…”
mentioning
confidence: 99%
“…(18) exhibits logarithmic singularities. To prevent this nonphysical behavior of T Ω the regularity condition dT Ω /dθ ′ | θ ′ =π(1−Ω)/2 = 0 must hold [23]. In order to derive the boundary condition for eq.…”
mentioning
confidence: 99%
“…r H i l (for brevity, we omitted the arguments i and l). Next, defining p i i; l t i i; l = t 1 i; l t ÿ1 i; l and using the numerical procedure developed in [16], we performed a Monte Carlo simulation of the magnetization h t i induced by the rotating field in two-dimensional systems of dipolar interacting nanoparticles.…”
mentioning
confidence: 99%
“…5 is that it does not use the Monte Carlo approach, so the last complicated problem does not appear. This feature of the method and its applicability to the study of magnetic relaxation over ten decades of time 5 make it a very useful tool in this domain.…”
mentioning
confidence: 99%
“…5 to study the magnetic relaxation in 2D ensembles of dipolar interacting nanoparticles subjected to a bias magnetic field. We have demonstrated its efficiency for the analysis of the relaxation law features arising from the mutual action of the dipolar correlations and bias field for different ensembles of Co nanoparticles and we have shown that the correlation effects play an important role in magnetic relaxation on all times.…”
mentioning
confidence: 99%
See 1 more Smart Citation